Twenty‐Four‐Month Outcomes of Heparin‐Bonded Covered Stents and Drug‐Coated Balloon Angioplasty in Femoropopliteal Artery Occlusion - Yuhao Lin; Yaowen Chang; Jing Wang; Huijun Yuan; Feng Zhang; Ruipeng Zhang; Jianjun Quan; Jian Dong; Yang Han; Longlong Cong; Lin Yang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The clinical outcomes of comparing covered stents (CSs) and drug‐coated balloons (DCBs) angioplasty in femoropopliteal artery occlusion remain unknown. This study aimed to evaluate the midterm efficacy of CS and DCB procedures in patients with FPO. Methods All 194 patients were divided into CS (94 patients) and DCB (100 patients) groups in this multicenter retrospective study. The primary end point was primary patency at 24 months, and the secondary end points included freedom from clinically driven target lesion revascularization, limb salvage, major adverse events, and overall survival rates. Propensity score matching analysis was performed to reconfirm the main end points. Results Compared with the patients in the DCB group, those in the CS group had a lower prevalence of smoking (54.3% versus 74.0%, P=0.004) and diabetes (38.3% versus 66.0%, P<0.001) before propensity score matching. Compared with the DCB procedure, the CS procedure resulted in a significantly greater primary patency at 24 months (74.4% versus 55.8%, P=0.019), with comparable primary patency at 12 months; similar results were obtained after matching. However, there was no difference in terms of clinically driven target lesion revascularization, limb salvage, major adverse events, or overall survival rates. Subgroup analyses confirmed the superior clinical patency of CS in patients with diabetes (P=0.010) and proximal reference vessel diameter ≥5.0 mm (P=0.038). A baseline ankle brachial index <0.40 was likely to be an independent risk factor for restenosis, and a postprocedural ankle brachial index ≥0.80 and the CS used (hazard ratio [HR], 0.54 [95% CI, 0.32–0.91], P=0.021) were potential protective factors for restenosis after multivariate analysis. Conclusions Compared with the DCB procedure, the CS procedure resulted in greater primary patency at 24 months in complicated femoropopliteal artery occlusion lesions.